Salvage: Gendered Violence in Activist Communities - Downes, Julia (2016)
How to best deal with sexual violence in radical social movements is a contentious issue in the UK Left. The persistence of and inability to deal with sexual violence contradicts the core values of equality and social justice at the heart of radical social movements. A legacy of being marginalised and subjected to state repression and scrutiny has led radical activist communities to develop important self-protective strategies to establish trust and belonging. Safer spaces policies, transformative justice and community accountability processes have been attempted to address gendered violence without recourse to the state. Debate has focused on the effectiveness and negative impacts of these interventions often at the expense of survivors and anti-violence activists. However, safer spaces policies and accountability processes are set up to fail without a critical exploration of wider power relations and self-protective cultural practices that already frame activist communities. We chose to develop knowledge and understanding about gendered violence in activist communities from the perspectives and experiences of survivors. Our project has a particular focus on exploring the experiences of women, transgender and non-binary individuals. August 2015 and January 2016 we interviewed 10 survivors who had experienced sexual violence within a range of different activist groups and communities across the UK. These accounts map out how layers of silence and denial can work in activist groups and communities to allow and maintain violence, abuse and harm. There was little evidence of a ‘one size fits all’ solution. Instead there is a need to better recognise how intersections of cissexism, homophobia, classism, racism, sexism and ableism shape survivors’ experiences and meanings of harm, available resources and solutions, and impacts of harm on individuals and communities. Understanding what can produce a ‘conducive context’ for sexual violence against women, transgender and non-binary individuals in activism offers crucial clues in how we can undo these harms. Progressive change requires no less than a reconceptualisation of culture that recognises violence as embedded in an ongoing struggle for power and control of activist arenas